Scanning electron microscopy of Antarctophthirus microchir (Phthiraptera: Anoplura: Echinophthiriidae): Studying morphological adaptations to aquatic life - Leonardi, María Soledad; Crespo, Enrique Alberto; Raga, Juan Antonio; Fernández, Mercedes (Micron)
The members of the Family Echinophthiriidae (Phthiraptera: Anoplura) are unique among insects because they infest hosts with an amphibious lifestyle. During their evolution they developed morphological traits that are reflected in unique features. The SEM is a helpful tool to analyze them. Knowing in detail the external structure of these lice is the first step to understand the whole process that derived from the co-adaptation of lice and pinnipeds to the marine environment. For the first time, we studied the external structure of all stages of an echinophthiriid louse. The results are discussed in the light of their evolutionary, functional, and ecological implications. Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Raga, Juan Antonio. Universidad de Valencia; España Fil: Fernández, Mercedes. Universidad de Valencia; España